Contemporary Business Ethics: Challenges, Frameworks, and Applications in the Modern Global Economy - Bakhita, Rona Maulidia; Sikki, Nurhaeni; Fauziah, Fauziah; Pramudani, Nadia; Agustini, Agustini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid evolution of global commerce, digitalization, and socio-political changes have fundamentally reshaped the landscape of business ethics in the 21st century. Contemporary business ethics goes beyond traditional notions of compliance and corporate responsibility, incorporating new considerations such as sustainability, diversity, data privacy, artificial intelligence governance, and stakeholder engagement. This paper critically examines the major dimensions of contemporary business ethics, analyzes emerging ethical challenges in global markets, reviews theoretical frameworks guiding ethical decision-making, and presents practical applications for organizations aiming to embed ethics into their strategic operations. Through an integrative literature review and case analysis, the study demonstrates that ethical leadership, transparency, and stakeholder inclusivity are critical for achieving long-term corporate resilience and social legitimacy.